STUDI LITERATUR TENTANG INTERAKSI SOSIAL REMAJA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine theoretical concepts, types of social interaction, forms of adolescent social interaction. The research method used is literature review, which uses textbooks or e-books and journals as a source of the required research data. The research object used was teenage students. The results of this study indicate that the theoretical concept of social interaction has been found. The theoretical concept of social interaction is Levinger's theory, Heider's theory or symbolic interaction theory and even Action Theory. The social interaction of adolescents is currently considered less face-to-face interaction, this generation is more engaged in virtual interactions through social media, many of the teenagers currently rely heavily on social media facilities such as WhatsApp, Twitter, Instagram, Facebook, Messangger, Wechat, Telegram, etc. As a medium of interaction with peers, teachers and even parents.Key Words: Literature review, Adolescent social interactions, social media